OP0137 GENOME-WIDE WHOLE-BLOOD TRANSCRIPTOME PROFILING IN A LARGE EUROPEAN COHORT OF SYSTEMIC SCLEROSIS PATIENTS. (2nd June 2020) - Beretta, L.; Barturen, G.; Vigone, B.; Bellocchi, C.; Hunzelmann, N.; Delanghe, E.; Kovács, L.; Cervera, R.; Gerosa, M.; Ortega Castro, R.; Almeida, I.; Cornec, D.; et al.
Abstract : Background: The analysis of annotated transcripts from genome-wide expression studies data is of paramount importance to understand the molecular phenomena underlying the occurrence of complex diseases, such as systemic sclerosis (SSc). Objectives: To perform whole-blood transcriptome and pathway analysis on whole-blood (WB) RNA collected in two cohorts of European SSc patients. Via a discovery and validation strategy we aimed at characterizing the molecular pathways that differentiate SSc from controls and that are reproducible in geographically diverse populations. Methods: WB samples from 252 controls and 162 SSc patients were collected in RNA stabilizers. Patients were divided into a discovery (n=79; Southern Europe) and validation cohort (n=83; Central-Western Europe). RNA sequencing was performed by an Illumina assay. Functional annotations of Reactome pathways were performed with the FAIME algorithm. In parallel, a immunophenotyping analysis on 28 circulating cell populations was assessed. We then tested: the presence of differentially expressed genes or pathways and the correlation between absolute cell counts and RNA transcripts/FAIME scores in regression models. Results significant in both populations were considered as replicated. Results: A total of 15224 genes and 1277 related functional pathways were available for analysis. Among these, 99 genes and 225 pathways were significant in both sets. The heatmap in figure shows the relative expression of replicated pathways and the distribution of cases and controls (red and green bars). Among the significant pathways we found a deregulation in: type-I IFN, TLR-cascade and signalling, function of the tumor suppressor p53 protein, platelet degranulation and activation. Correlation analysis showed that the count of several cell subtypes is jointly associated with RNA transcripts or FAIME scores with strong differences in relation to the geographical origin of samples; neutrophils emerged as the major determinant of gene expression in SSc-whole-blood samples. Conclusion: We discovered a set of differentially expressed genes and pathways that could be validated in two independent sets of SSc patients highlighting a number of deregulated molecular processes that have relevance for the pathogenesis of autoimmunity and SSc. Acknowledgments: This work was supported by EU/EFPIA/Innovative Medicines Initiative Joint Undertaking PRECISESADS grant No. 115565. Disclosure of Interests: Lorenzo Beretta Grant/research support from: Pfizer, Guillermo Barturen: None declared, Barbara Vigone: None declared, Chiara Bellocchi: None declared, Nicolas Hunzelmann: None declared, Ellen Delanghe: None declared, László Kovács: None declared, Ricard Cervera: None declared, Maria Gerosa: None declared, Rafaela Ortega Castro: None declared, Isabel Almeida: None declared, Divi Cornec: None declared, Carlo Chizzolini Consultant of: Boehringer Ingelheim, Roche, Jacques-Olivier Pers: None declared, Zuzanna Makowska Employee of: Bayer AG, Anne buttgereit Employee of: Bayer AG, Ralf Lesche Employee of: Bayer, Martin Kerick: None declared, Marta Alarcon-Riquelme: None declared, Javier Martin Ibanez: None declared